Upaya Pembebasan Hak Atas Tanah di Pasar Pagi Samarinda: Tinjauan Hukum Berdasarkan UU No. 2 Tahun 2012 - Putri, Nadia Ade; Mukti, Hudali (International Journal of Politic, Public Policy and Environmental Issues, 2024)
The acquisition of land rights is a crucial issue in public infrastructure development in Indonesia, including in Samarinda City, where the revitalization project of Pasar Pagi requires the acquisition of land with ownership certificates. This study aims to analyze the efforts of the Samarinda City Government in acquiring land rights and the obstacles faced in the process. Employing an empirical juridical method with a qualitative approach, this research involves interviews with landowners and related institutions. The findings indicate that the government's efforts in land acquisition are not optimal, with the main obstacles being the rejection of landowners regarding compensation deemed insufficient and the lack of community involvement in planning. Therefore, the Samarinda City Government needs to enhance communication and transparency in the land acquisition process to achieve mutually beneficial agreements.